The happiness of heaven - Boudreaux, F. J. (Andrews UK, Ltd., 2012)
A fascinating look at the Catholic concept of Heaven. From the preface:Many books, owing to their special character, are designed for only a small circle of readers. But topics involving general and vital interests deservedly claim the attention of all persons. Such is the subject of the present work-""The Happiness of Heaven."" For who is he that, believing in the existence of that blessed abode, does not hope eventually to arrive there?What sublime descriptions do not the Holy Scriptures give us of the blessed City of God! Her wails are built of jasper-stone; but the City itself is of pure an.